2023
DOI: 10.3390/bioengineering10030322
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Antigen Tests during the COVID-19 Era in Korea and Their Implementation as a Detection Tool for Other Infectious Diseases

Abstract: Rapid antigen tests (RATs) are diagnostic tools developed to specifically detect a certain protein of infectious agents (viruses, bacteria, or parasites). RATs are easily accessible due to their rapidity and simplicity. During the COVID-19 pandemic, RATs have been widely used in detecting the presence of the specific SARS-CoV-2 antigen in respiratory samples from suspected individuals. Here, the authors review the application of RATs as detection tools for COVID-19, particularly in Korea, as well as for severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 99 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…Many studies have reported methods and technologies developed for detecting and treating COVID-19 that can be extended to future outbreaks. The COVID-19 pandemic has widely utilized rapid antigen tests (RATs) to detect the SARS-CoV-2 antigen [21]. These tests have been valuable due to their simplicity and rapid results.…”
Section: Biofets As Promising Biosensors For Covid-19 and Future Pand...mentioning
confidence: 99%
“…Many studies have reported methods and technologies developed for detecting and treating COVID-19 that can be extended to future outbreaks. The COVID-19 pandemic has widely utilized rapid antigen tests (RATs) to detect the SARS-CoV-2 antigen [21]. These tests have been valuable due to their simplicity and rapid results.…”
Section: Biofets As Promising Biosensors For Covid-19 and Future Pand...mentioning
confidence: 99%
“…Antigen tests can be used for the rapid prevention of community-acquired infections by enabling quick identification of SARS-CoV-2 infection (approximately 15 min of test time) [ 14 ]. However, the sensitivity of antigen tests is lower than that of NAATs, especially in asymptomatic patients [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%